2014
DOI: 10.1186/2049-1891-5-4
|View full text |Cite
|
Sign up to set email alerts
|

The influences of SE infection on layers’ production performance, egg quality and blood biochemical indicators

Abstract: BackgroundSalmonella enterica serovar Enteritidis (SE), as a major cause of foodborn illness, infects humans mainly through the egg. However, the symptom of laying hens usually is not typical and hard to diagnosis. In the present study, it is studied that the influences of SE infection on layers’ performance, egg quality and blood biochemical indicators. It will help us to improve the strategy to control SE infection in commercial layers. One hundred layers at 20 wk of age were divided into 2 groups, 60 hens f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 48 publications
(49 reference statements)
1
11
0
Order By: Relevance
“…However, after the challenge higher GOT values were found in birds which had received NEOX or positive control while probiotics lowered the GOT value especially for TOYO group. This finding agrees with [15] who reported that colonization of Salmonella in organs increases the liver enzyme activities in blood. Several studies have assessed the effects of Salmonella on the gene expression of chicken immune tissues or cells [16,17].…”
Section: Discussionsupporting
confidence: 93%
“…However, after the challenge higher GOT values were found in birds which had received NEOX or positive control while probiotics lowered the GOT value especially for TOYO group. This finding agrees with [15] who reported that colonization of Salmonella in organs increases the liver enzyme activities in blood. Several studies have assessed the effects of Salmonella on the gene expression of chicken immune tissues or cells [16,17].…”
Section: Discussionsupporting
confidence: 93%
“…AST mainly exists in cardiomyocytes, followed by hepatocytes [ 24 ]. ALT is present in high concentration in hepatocytes, it’s the specific marker of hepatocellular injury because it occurs exclusively in the liver [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alanine aminotransferase and aspartic aminotransferase exist in hepatocytes in high concentration and the latter is also mainly present in cardiomyocytes ( Fan et al, 2014 ). If hepatic cells or myocardial cells are destroyed, above enzymes will leak into the blood and levels of these will increase rapidly ( Kew, 2000 ; Fan et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%